Reliability of lower extremity kinematics in three-dimensional gait measurements in children with cerebral palsy - Ricardo, Diogo (2021)
Background: Cerebral Palsy is a complex pathology that describes a group of motor disorders with different presentations and functional levels. Three-dimensional gait analysis is used in the assessment of CP children to assist in clinical decision-making and assessing outcomes in the rehabilitation process. Due to the CP intra-subject gait variability, it’s crucial to access the repeated gait measurements to evaluate the response to therapeutic interventions in the rehabilitation process. Aim of the study: The objective of this study was to determine the intra-subject measurement reliabilities of the kinematic parameters of children with hemiplegic and diplegic types of cerebral palsy.